Structural and functional effects of manipulating the degree of methylesterification in a model homogalacturonan with a pseudo-random fungal pectin methylesterase followed by a processive methylesterase. (April 2018) - Kim, Yang; Cameron, Randall G.; Williams, Martin A.K.; Luzio, Gary A.
Abstract: We explored the possibility of controlling charge distribution in the homogalacturonan regions of pectin to produce a population of demethylesterified molecules with desirable functional properties by utilizing consecutive treatments with pectin methylesterases (PME) having different modes of action. A fungal PME from Aspergillus aculeatus ( Aa -PME), with a pseudo-random mode of action, was used to demethylesterify a extremely high methylesterified HG (DM 94%, average degree of polymerization 246) by reducing the degree of methylesterification (DM) from 94% to either 70% or 80%. A second demethylesterification step, to 50% DM, was performed using a processive PME from Carica papaya ( CpL -PME). Introduced demethylesterified blocks were released either by exhaustive or limited endo polygalacturonase (EPG) digestion. Degree of blockiness (DB), absolute degree of blockiness (DBabs ), average demethylesterified block size ( B S ¯ ) and number of average sized demethylesterified blocks per molecule ( B N ¯ ) were estimated. B S ¯ and B N ¯ as well as DB/DBabs differed depending on the initial DM reduction by Aa PME, the number of activity units of CpL PME used and the reaction pH ( P  < 0.05). Consecutive demethylesterification of HG by AaPME to 80% DM and then by CpL PME to 50% DM at pH 4.5 produced significantly longer oligomer blocks compared to Aa-PME demethylesterification to 70% DM followed by CpL -PME to 50% DM at pH 7.0. Limited EPG digestion released nearly intact demethylesterified blocks and the released oligomers were coupled with in silico modeling. Resulting oligomer distribution corresponded to the in silico mode of action representing contiguous demethylesterification of 10 GalA residues rather than that of random or complete block-wise demethylesterification. Calcium-mediated gels of the modified HGs displayed G′ higher than G″ values and both moduli differed significantly according to the amount of CpL PME applied even though their final DMs were identical. These results suggest the possibility of controlling B S ¯ and engineering a population of demethylesterified pectin molecules with specified demethylesterified B S ¯ and functional properties. Graphical abstract: Image 1 Highlights: A fungal and a plant pectin methylesterase were sequentially applied to a model homogalacturonan. Average demethylesterified block size and number differed based on the treatment. A processive multiple attack mode of action best explained block distributions. Significant correlations between B S ¯, B N ¯, degree of blockiness and G′ were observed. Functional properties could be customized using PMEs of different mode of actions.